THE INFLUENCE OF DEMAND PLANNING, ORDERING STRATEGY, AND INFORMATION SYSTEMS ON THE EFFECTIVENESS OF INVENTORY CONTROL AT PT ERICO INDONESIA - Budi Susanto; Erna Mulyati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
Inventory management in the processed food distribution industry—characterized by limited shelf life—requires accurate demand planning, an effective ordering strategy, and an integrated information system to ensure product availability while preventing resource inefficiency. This study analyzes the influence of these three factors on inventory control effectiveness at PT Erico Indonesia and tests a conceptual model that integrates demand planning, ordering strategies, and information systems. The findings are expected to be generalizable to similar distribution environments managing perishable products with strict shelf-life policies. The company faces recurring issues of overstock and stockout, resulting in increased storage costs and decreased sales potential. This research uses an explanatory quantitative approach with confirmatory characteristics, employing Partial Least Squares–Structural Equation Modeling (PLS-SEM) via SmartPLS. The population consists of employees involved in demand planning, ordering, information system management, and inventory control. Using purposive sampling, 65 respondents were included. Results indicate that the information system has a positive and significant effect on inventory control effectiveness, while demand planning and ordering strategy show positive but insignificant effects. The study also demonstrates that these three variables simultaneously contribute to explaining the variation in inventory control effectiveness. These findings highlight the importance of a reliable and integrated logistics information system to improve data accuracy, accelerate stock information access, and support responsive decision-making in managing products with limited shelf life.